2016
DOI: 10.1177/0095327x16629160
|View full text |Cite
|
Sign up to set email alerts
|

“Managing the Migration From Military to Civil Society”

Abstract: An estimated 70,000 personnel are annually released at the prime of life from the Indian armed forces to maintain a youthful service profile. The migration of veterans in search of a second career to civil society involves managing crucial socioeconomic needs. This article examines the resettlement needs of veterans using survey research which measured resettlement needs of air force veterans in two distinct districts (regions) in India ( N = 400). The analysis reveals that the educational needs of dependent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In contrast, the ESM, who could not find jobs, faced a shortage of funds, challenging domestic and personal issues ended up having a problematic transition and unhappy life. The results support the findings of Black and Papile (2010) and Maharajan and Krishnaveni (2016). The government resettlement agencies are perceived ineffective and of little use, and the majority of ESMs claimed that they found jobs with their own efforts.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the ESM, who could not find jobs, faced a shortage of funds, challenging domestic and personal issues ended up having a problematic transition and unhappy life. The results support the findings of Black and Papile (2010) and Maharajan and Krishnaveni (2016). The government resettlement agencies are perceived ineffective and of little use, and the majority of ESMs claimed that they found jobs with their own efforts.…”
Section: Discussionsupporting
confidence: 84%
“…A previous study described four themes, that is, personal integration, family integration, work integration and cultural integration (Blais, Thompson, & McCreary, 2009) for complete and successful reintegration. Resettlement requirements of military retirees involve both social and financial aspects (Maharajan & Krishnaveni, 2016), so an ESM needs to have a second career in civilian life. However, social elements of integration are essential but rarely considered.…”
Section: Integration Processmentioning
confidence: 99%
“…The response rates varied across the studies, and lower response rates could increase the bias evident within the sampling strategy as it is more difficult to claim that the participants represent a wider population (Bryman, 2012). A high response rate would have been greater than 70% (Greenhalgh, 2010), and only two studies included within this review reported a high response rate (Maharajan & Krishnaveni, 2016;Mangum & Ball, 1989).…”
Section: Experience Of Work Transition Of Veterans Who Became Nurse A...mentioning
confidence: 99%
“…Two studies also checked the internal consistency of their measurement tools (Baruch & Quick, 2007;Vigoda-Gadot, Baruch, & Grimland, 2010), this means they demonstrated that the tool reliably measured the main constructs of interest with their specific sample (Polit & Beck, 2012). Of note, one study made no reference to the measurement tool (Maharajan & Krishnaveni, 2016). However, in general, it is likely that most of the included quantitative papers carried out statistical analysis informed by data measurements that were relevant to their study focus, thus leading to meaningful findings.…”
Section: Experience Of Work Transition Of Veterans Who Became Nurse A...mentioning
confidence: 99%
“…This is important because maintaining civilian employment may lead to socio-economic stability. A survey of Indian air force veterans ranked employment as the second most important socioeconomic need after children's education [25]. One factor that may promote successful career transition and job security was skills transfer.…”
Section: Successful Career Transitionmentioning
confidence: 99%